Value education in and through university education: The Gandhian perspective - Mishra, Anil Dutta (2010)
Without morality and without ethics, no student, in real sense, can be considered to be healthy in mental and physical terms, because for it, self-control and good character are essential. Moral and ethical knowledge is the focal point on which Mahatma Gandhi's concept of value education is based. The attainment of spiritual growth that has been described by Mahatma Gandhi, as an essential part of education, can only be gained through these values. To revive the value-education in universities and convert them into action there is no need for the establishment of new or separate university or department. But the need of the hour is to strengthen the existing institutions and for that the existing institutions should start value-oriented programmes and greater importance should be given to incorporate social activities. - Reproduced.
Keywords: Universities; Education; Values education